A Garden of Marvels : Tales of Wonder from Early Medieval China - Campany, Robert Ford (Book collections on Project MUSE., 2015)
"Between 300 and 600 C.E., Chinese writers compiled thousands of accounts of the strange and the extraordinary. Some described weird spirits, customs, and flora and fauna in distant lands. Some depicted individuals of unusual spiritual or moral achievement. But most told of ordinary people's encounters with ghosts, demons, or gods; sojourns in the land of the dead; eerily significant dreams; and uncannily accurate premonitions. The selection of such stories presented here provides an alluring introduction to early medieval Chinese storytelling and opens a doorway to the enchanted world of thought, culture, and religious beliefs of that era. Known as zhiguai, or "accounts of anomalies," they convey a great deal about how people saw the cosmos and their place in it. The tales were circulated because they were entertaining but also because their compilers meant to document the mysterious workings of spirits, the wonders of exotic places, and the nature of the afterlife. A collection of more than two hundred tales, A Garden of Marvels offers an authoritative yet accessible introduction to zhiguai writings, particularly those never before translated or adequately researched"--